2015
DOI: 10.1002/jsfa.7034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and nitrogen supply on the quality and health‐related compounds of strawberry fruits (Fragaria × ananassa cv. Primoris)

Abstract: The use of low-quality waters, such as those found in Almeria (salinity, N9S and N5S) and low nitrogen inputs (N5, avoid environmental impact) for strawberry cultivation does not exert a negative impact on overall quality. Positive differences could be found in SSC, firmness and health-related compounds when compared against the control treatment (N9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
4
29
1
2
Order By: Relevance
“…In addition, Cardeñosa et al. () reported that vitamin C content of cv. Primoris cultivated in soilless system was 0.20–0.25 mg g −1 , which was much lower than our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cardeñosa et al. () reported that vitamin C content of cv. Primoris cultivated in soilless system was 0.20–0.25 mg g −1 , which was much lower than our results.…”
Section: Resultsmentioning
confidence: 99%
“…The Vitamin C content in ripe strawberries was reported ranging from 0.19 g kg −1 to 1.1 g kg −1 , for cultivars "Albion," "Campineiro," "Chandler," "Camarosa," and "Selva" (Pérez et al 1997;Cordenunsi et al 2005;Nunes et al 2006;Ferreyra et al 2007;Kafkas et al 2007). In addition, Cardeñosa et al (2015) reported that vitamin C content of cv. Primoris cultivated in soilless system was 0.20-0.25 mg g −1 , which was much lower than our results.…”
Section: Effect Of the Variety On Quality Characteristicsmentioning
confidence: 99%
“…Therefore, the SSC/TA ratio was the focus of this study. Previous studies have shown that N, P, K, and water have significant effects on the yield and fruit quality of strawberry [27,[55][56][57][58]. We used a quadratic regression orthogonal rotation combination experimental design to investigate the optimal fertilization and water combination for high strawberry yield and best fruit quality (optimal SSC/TA ratio).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that N, P, K, and water have significant effects on the yield and fruit quality of strawberry [27,5255]. A quadratic regression orthogonal rotation combination experimental design was used to investigate the optimal fertilization and water combination for high strawberry yield and best fruit quality with optimal SSC/TA ratio.…”
Section: Discussionmentioning
confidence: 99%